Antagonist rescue of agonist IVF cycle at risk of OHSS: a case series. (February 2014) - Martínez, Francisca; Mancini, Fulvia; Solé, Miquel; José Gomez, Maria; Beatriz Rodríguez, Dalia; Buxaderas, Rosario; Rodriguez, Ignacio; Nolasc Barri, Pedro
Abstract We describe a series of in vitro fertilisation (IVF) long protocol cycles presenting a risk of ovarian hyperstimulation syndrome (OHSS) which were rescued with an antagonist at a university-based tertiary-care fertility centre. Nineteen IVF patients presenting a risk of OHSS during treatment with long protocol, between 2009 and November 2012 were included in the present study. After discussion of available options, the agonist was stopped and a daily gonadotropin-releasing hormone (GnRH) antagonist injection was initiated ("rescue protocol") and maintained until ovulation trigger. Fourteen patients were triggered with human chorionic gonadotropin (hCG) and five with GnRH agonist bolus, yielding competent oocytes. Seventeen embryo transfers were performed in the fresh cycles. One patient developed moderate OHSS. There were eight clinical pregnancies after the fresh IVF cycle (42% per patient), and six further pregnancies after frozen-thawed cycles, resulting in a 73% cumulative clinical pregnancy rate within one year. We conclude that the "rescue protocol with antagonist" of the long IVF cycle with a high risk of OHSS allows us to carry on with the cycle, without compromising its success or the patient safety, thus broadening the possibility of applying the long protocol.